Proses Kreatif Abah Olot dalam Melestarikan Karinding - R. Muhammad Luthfi Ferrari; Heri Herdini; Suhendi Afryanto (Pascasarjana ISBI Bandung, 2022)
Karinding is an entertaining instrument made of palm midrib or bamboo which has long flat form similar to fork. In recent years, karinding has been considered to be a musical instrument which can be played together with common musical instruments. Karinding was once temporarily extinct in Sundanese cultural society until resurrected in 2003. This emergence was mainly by creativity of Abah Olot who has been trying to revive and reinvent several Sundanese traditional musical instruments like celempung that has been developed into celempung rèntèng and melodic celempung. Besides, Abah Olot also modified kohkol into kohkol latung. This is all for his mission to resurrect and to make karinding more appealing to modern cultural society. In line with this, Abah Olot created a musical group called Giri Kerencèng which combined karinding with his reinvented Sundanese traditional musical instruments. This writing reveals Abah Olot’s creativity. The existentialism theory is used in the discussion. Existentialism Hasbunallah wani’malwakiil are two basic concepts. First, the being-in-the-world concept and secondly is the nonbeing concept. This writing is written to describe how Abah Olot’s existence in preserving and developing karinding as Sundanese traditional musical instrument and it’s impact both to the musical instrument itself and the societies.Keyword: Karinding, AbahOlot, Creativity, Existence